Keefektifan Ice Breaking dalam Mengembalikan Fokus dan Motivasi Belajar Siswa Kelas V di SD Negeri 004 Pulau Payung - Rahmad Danil (Mahaguru: Jurnal Pendidikan Guru Sekolah Dasar, 2023)
Ice Breaking is a simple activity designed to change the atmosphere in a learning environment from dull, rigid, and drowsy to one that is active, enthusiastic, and spirited. It is meant to build an engaging and vibrant learning atmosphere. This research aims to investigate the influence of Ice Breaking in rekindling the focus of 5th-grade students at Public Elementary School 004 on Pulau Payung. The research employs a qualitative approach, specifically a descriptive-qualitative study. The instrument used for this research is a questionnaire. Data collection was conducted by distributing the questionnaire directly to the elementary school students. In this research, data analysis employed a four-category Likert scale, which included "Strongly Agree (SA)," "Agree (A)," "Disagree (D)," and "Strongly Disagree (SD)." From these four categories, ten statements were devised for the participants to complete. These categories were then grouped into two responses: positive and negative. The research findings revealed that out of 16 students in the 5th grade at Public Elementary School 004 on Pulau Payung, who chose the "Agree" option in response to the impact of ice breaking on enhancing focus and learning motivation, they are considered to have responded positively. This is evident in the percentage of positive responses (Strongly Agree and Agree) at 92.5%, with a 7.5% rate for negative responses (Disagree and Strongly Disagree).